Unpacking Legal Accountability: The Case of the European Central Bank - Mark Dawson; Ana Bobić (Politics and Governance)
Although the term “legal accountability” increasingly appears in scholarly discourse surrounding the European Central Bank (ECB), it is under-theorised. This article explores three different dimensions of legal accountability, which are often confused. Accountability to law refers to accountability to legal rules and standards. Accountability through law refers to achieving routes of administrative and political accountability through legal institutions. Accountability of law implies the accountability of legal institutions themselves to the wider public (and other courts) for their decisions. We argue that these dimensions are deeply connected in the sense that either improvements or failures along one dimension are easily carried to the others. We demonstrate the argument by applying our concept of legal accountability to ECB activity, comparing judicial review in the context of monetary policy with the Single Supervisory Mechanism. These cases suggest a possible vicious rather than virtuous circle of legal accountability, i.e., a tendency for either unclear legal standards or lack of accountability of courts themselves to undermine accountability for ECB activity as a whole.